DOE Based Statistical Approaches in Modeling of Laser Processing – Review & Suggestion - Sivarao, Subramonian; Salleh, Mohd Shukor; T., Joseph Sahaya Anand; Abd Rahman, Ammar (IJENS Publishers, 2010)
Design of Experiment commonly referred to as DOE is one of the extensively used methods for experimental study of many processes in engineering. It is a statistical approach in which a mathematical model is developed through experimental runs. DOE provides us the opportunity to optimize and predict possible output based on the parameters setting. In this study, a review is done on DOE techniques that have been employed for laser beam process optimization by other researches. This study predominantly focuses on the usage of response surface methodology, Taguchi’s method and factorial design in laser beam machining. A deduction is made to illustrate the significance of machining parameters to responses.